THE IMPORTANCE OF COMPETENCE IN WORKING WITH INFORMATION IN PHYSICAL SCIENCE - Saidaxon Mamasidiqova (Journals Park Publishing, 2022)
The article will talk about the competence and its importance in working with information in teaching physics. The relevance of the topic is now in the importance and relevance of physical science.
Keywords: physics, innovations, education, teaching, competence.